Are you a journalist? - Fulton, Janet (Javnost (Ljubljana), 2015)
This article reports on findings from a research project that is examining alternative paths for media producers. The researcher has interviewed media producers in the digital space, including bloggers, online magazine producers, broadcasters and website producers, to discover what skills are required to work in a digital space, what business models are successful and what technologies are being employed. One of the questions asked of each of the respondents was "Do you consider what you are doing journalism?" Responses have shown that there is often a particular view of journalism and what it is and who can be called a journalist: those who have worked as journalists in traditional media still call themselves journalists while others who have come into the space via other professions are cautious about using the term. The article draws on the respondents' comments from the research in an attempt to further understand how such definitions around journalism and journalist are informing media producers and their understanding of these terms in a splintering media epoch.
Keywords: Alternative mass media; Alternativni mediji; Digital media; Elektronski mediji; Journalism; New technologies; Nove tehnologije; Novinarstvo